A política social de economia solidária : um estudo de caso do município de São Carlos - Capacle, Camila (2010)
The Solidary Economy is a practice of generating employment and income, existing in thousands of Brazilian municipalities and communities, and over a hundred of city halls have been investing efforts and human, physical and financial resources in this alternative. The Solidary Economy has won status of national policy, but faces the great challenge of consolidate itself as a State policy. This work aims to analyze the municipality of Sao Carlos public policy of Solidary Economy between the years of 2001 to 2009. From the analysis of public policies methodology and redoing the trajectory of the social policies in Brazil, the research seeks to show up the social construction of Solidary Economy as a public policy, presenting a model of this policy in municipal/local level. The analysis of Sao Carlos policy of Solidary Economy demonstrates the existence of guidelines on the implementation and consolidation of Solidary Economy as a State policy, with prominence for three points: the creation and approval of a Legal Mark; the establishment and utilization of financial Founds of policy and, finally, the social and political organization of the solidary enterprises and the social movement. However, despite the construction of these jurisdictions in the municipality, we verified that the universality and range which characterize a public policy just are possible through a National Unique System, with public sponsorship and mechanisms of relation and induction between federative beings.